Near-infrared light response type nano enzyme as well as preparation method and application thereof

By developing near-infrared light-responsive nanoenzymes, using the composite structure of Ag3PO4 nanoparticles and Ag2S quantum dots, the ratio of surfactant is optimized, and the problems of low catalytic efficiency and insufficient spatiotemporal controllability of existing nanoenzyme antibacterial materials are solved. It has achieved efficient prevention of bacterial infection and biofilm formation of implanted materials.

CN119455115APending Publication Date: 2025-02-18CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411694113.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing nanoenzyme antibacterial materials have low catalytic efficiency, insufficient controllability in time and space, and poor tissue penetration ability, resulting in toxic side effects and bacterial resistance problems in preventing bacterial infection of implanted materials.

Method used

Develop near-infrared light-responsive nanoenzymes to form Ag3PO4 nanoparticles in the reaction of silver ions, hexamethylenetetramine, Ag2S and phosphate, and encapsulate them with polyvinylpyrrolidone K30 to optimize the surfactant addition ratio to Improve the catalytic activity and controllability of nanoenzymes.

Benefits of technology

It has achieved effective prevention of bacterial infection and biofilm formation on the surface of the implanted material, with high catalytic activity, temporal controllability and biocompatibility, avoiding the occurrence of bacterial drug resistance, and reducing toxic side effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005151708560000011
    Figure HDA0005151708560000011
  • Figure HDA0005151708560000012
    Figure HDA0005151708560000012
  • Figure HDA0005151708560000021
    Figure HDA0005151708560000021
Patent Text Reader

Abstract

The invention relates to the technical field of biological medicines, in particular to a near-infrared light response type nano-enzyme as well as a preparation method and application thereof. The invention provides a near-infrared light response type nano-enzyme material, which is composed of Ag2S, Ag3PO4 and a surfactant, has the characteristics of good space-time controllability, high catalytic activity and good biocompatibility in prevention of bacterial infection of implant materials and biofilm formation, does not cause generation of bacterial drug resistance, and has high clinical transformation potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedicine technology, and in particular to near-infrared light-responsive nanozymes, preparation methods and applications thereof. Background Art

[0002] With the intensification of global aging and the improvement of people's health care awareness, the demand for orthopedic implant materials caused by orthopedic diseases continues to grow. However, once bacterial colonization, bacterial adhesion and surface biofilm formation occur on implant materials, serious complications such as infected bone defects and infected nonunion often occur, requiring multiple surgical debridements, and even leading to serious consequences such as secondary surgery to remove implants and amputation. Therefore, it is very important to avoid or reduce the occurrence of implant material infection and exert antibacterial function through surface antibacterial modification.

[0003] At present, in order to reduce the infection of implant materials, antibiotics are administered systemically for prevention in clinical practice. However, such regimens can cause poisoning symptoms and lead to the emergence of drug-resistant bacteria. Although some antibiotic-based implant material coatings have been developed to prevent bacterial infections, they face severe problems such as increased bacterial resistance and toxic side effects. In recent years, nanozyme-based antibacterial materials have attracted widespread attention from researchers. They can produce a large amount of reactive oxygen species at the site of infection, produce extremely high bactericidal activity and anti-biofilm formation capabilities, and avoid the emergence of bacterial resistance. However, nanozymes often face the problems of insufficient catalytic efficiency and poor controllability, which limits their further practical application.

[0004] Light-responsive nanozymes have excellent spatiotemporal controllability. Laser irradiation can effectively control and improve the catalytic activity of nanozymes in the target lesion area and reduce their toxic side effects in non-target areas. Therefore, the development of new light-responsive nanozyme materials for antibacterial coatings on the surface of implantable materials is an urgent problem to be solved. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a near-infrared light-responsive nanozyme, a preparation method and an application thereof.

[0006] The present invention provides a light-responsive nanozyme, which comprises: Ag2S, Ag3PO4 and a surfactant.

[0007] Furthermore,

[0008] The surfactants include polyethylene glycol and polyvinyl pyrrolidone (PVP);

[0009] The molecular weight of the polyethylene glycol includes: 400, 1000, 2000, 5000, 10000;

[0010] The polyvinyl pyrrolidone (PVP) includes: PVP K15, PVP K30, PVP K60 and PVP K90;

[0011] Specifically, in the present invention, Ag3PO4 particles combined with Ag2S (i.e., the black precipitate in the preparation of the nanozyme in Example 1) are mixed with the above-mentioned different surfactants respectively, and the addition ratio is optimized. The test results show that polyvinylpyrrolidone K30 (PVP K30) is optimal when the mass of Ag2S is 19.06% of the added mass of polyvinylpyrrolidone K30, and its dispersibility is the best.

[0012] The light-responsive nanozyme is a satellite structure with Ag3PO4 as the core.

[0013] The present invention provides a method for preparing the light-responsive nanozyme, which comprises the following steps:

[0014] Step 1, silver ions react with Ag2S and phosphate in the presence of hexamethylenetetramine to obtain Ag3PO4 particles combined with Ag2S;

[0015] Step 2: The Ag2S-bound Ag3PO4 particles are wrapped with polyvinylpyrrolidone K30 to obtain the light-responsive nanozyme.

[0016] Furthermore, in step 1 of the preparation method of the present invention,

[0017] The mass ratio of the salt compound containing the silver ion, hexamethylenetetramine, Ag2S, and the salt compound containing the phosphate is (0.1-0.5): (0.1-0.5): (180-200): (1.0-1.5).

[0018] Specifically, the mass ratio of the salt compound containing the silver ion, hexamethylenetetramine, Ag2S, and the salt compound containing the phosphate is (0.3-0.35): (0.3-0.35): (188-192): (1.1-1.4).

[0019] In a specific embodiment of the present invention, the mass ratio of the salt compound containing the silver ion, hexamethylenetetramine, Ag2S, and the salt compound containing the phosphate group is 0.318:0.315:190.8:1.27.

[0020] In the present invention,

[0021] The salt compound containing the silver ion includes silver chloride and / or silver nitrate, which is not limited in the present invention; in a specific embodiment of the present invention, it is silver nitrate;

[0022] The salt compound containing the phosphate radical includes metal phosphates, and the metal phosphates include sodium phosphate and / or potassium phosphate; in a specific embodiment of the present invention, the metal phosphate is potassium phosphate K3PO4.

[0023] The mass of the Ag2S is 5% to 50% of the mass of the polyvinylpyrrolidone K30, and further 15% to 25%; in the embodiment of the present invention, it is 19.6%; in the specific embodiment of the present invention, the mass of Ag2S is 19.06 mg, and the mass of PVP 30 participating in the reaction is 100 mg.

[0024] The Ag2S is prepared from silver diethyldithiocarbamate and dodecanethiol.

[0025] Specifically, in the present invention, the Ag2S is obtained by reacting silver diethyldithiocarbamate and dodecanethiol in the presence of octadecene to obtain Ag2S with dodecanethiol as a ligand; the Ag2S with dodecanethiol as a ligand can be dissolved in water after ligand replacement, which is convenient for subsequent reactions.

[0026] The mass ratio of silver diethyldithiocarbamate, dodecanethiol and octadecene is 1:60-80:200-500; further 1:75-80:350-450; in a specific embodiment of the present invention, it is 1:78.125:390.625.

[0027] After obtaining Ag2S with octadecene as a ligand, the method further comprises a precipitation step, wherein the precipitation reagent is acetone;

[0028] The ligand replacement is as follows: using N,N-dimethylformamide and chloroform as solvents, reacting in the presence of maleic acid, citric acid and N,N-dimethylformamide (DMF) to complete the replacement; the volume ratio of N,N-dimethylformamide to chloroform is 1:1;

[0029] The mass ratio of maleic acid, citric acid and Ag2S is (5-15): (0.2-2): (0.2-0.8); further (9-11): (0.5-1.5): (0.5-0.7); in the specific embodiment of the present invention, it is 10:1:0.6;

[0030] The present invention provides a near-infrared light-responsive nanozyme to solve the problems of low catalytic efficiency, insufficient spatiotemporal controllability, and poor tissue penetration of existing nanozyme antibacterial materials. The nanozyme has good controllability, strong tissue penetration, and high catalytic activity, and can effectively prevent bacterial infection of implanted materials without producing obvious toxic side effects. At the same time, the present invention adjusts the material ratio, parameter setting, and steps for obtaining the light-responsive nanozyme, and obtains the near-infrared light-responsive nanozyme as described in the present invention, which has better performance than other composites with other material ratios, parameters, and step settings. For example, in the light-responsive nanozyme of the present invention, the mass of Ag2S quantum dots is 6% of that of Ag3PO4 nanoparticles, and has the best light absorption capacity.

[0031] The present invention provides a nanozyme preparation, which includes an auxiliary material and at least one of the following I) to II):

[0032] 1), the light-responsive nanozyme of the present invention;

[0033] II), the light-responsive nanozyme prepared by the preparation method of the present invention.

[0034] The auxiliary materials include: buffer, antioxidant, buffer, pH regulator, thickener, antibiotic and / or preservative, etc.

[0035] The present invention provides an antibacterial composition, which comprises at least one of a) to c) and an antibacterial substance:

[0036] a), the light-responsive nanozyme of the present invention;

[0037] b) The light-responsive nanozyme prepared by the preparation method of the present invention;

[0038] c) The nanozyme preparation of the present invention.

[0039] Furthermore, the antibacterial substances include antibacterial peptides, antibiotics, sulfonamides, imidazoles, nitroimidazoles, quinolones and other chemically synthesized drugs, which are not limited in the present invention.

[0040] The present invention provides the use of at least one of the following i) to iii) in reducing bacterial infection and biofilm formation in implant materials:

[0041] i), the light-responsive nanozyme of the present invention;

[0042] ii), the light-responsive nanozyme prepared by the preparation method of the present invention;

[0043] iii), the nanozyme preparation of the present invention;

[0044] iv) The antibacterial composition of the present invention.

[0045] The present invention provides a method for reducing bacterial infection and biofilm formation, which comprises using at least one of the following A) to D):

[0046] A), the light-responsive nanozyme of the present invention;

[0047] B), the light-responsive nanozyme prepared by the preparation method of the present invention;

[0048] C), the nanozyme preparation of the present invention;

[0049] D) The antibacterial composition of the present invention.

[0050] Furthermore, the reducing of bacterial infection includes but is not limited to reducing bacterial infection on the surface of the implant.

[0051] The present invention provides a near-infrared light-responsive nanoenzyme material, which is composed of Ag2S, Ag3PO4 and a surfactant. It has the characteristics of good spatiotemporal controllability, high catalytic activity and good biocompatibility in preventing bacterial infection and biofilm formation of implant materials, and will not cause the development of bacterial resistance, and has high clinical transformation potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The preparation and light response principle diagram of the near-infrared light-responsive nanozyme of the present invention are shown;

[0053] Figure 2 1 is a transmission electron microscope image of the Ag2S quantum dots of Example 1 of the present invention;

[0054] Figure 3 1 shows a transmission electron microscope image of the Ag3PO4 nanoparticles of Example 2 of the present invention;

[0055] Figure 4 The scanning electron microscope image, transmission electron microscope image and particle size distribution diagram of the near-infrared light-responsive nanozyme of Example 2 of the present invention are shown; in the figure, a is a scanning electron microscope image, b is a transmission electron microscope image, c is a high-resolution transmission electron microscope image, d is an elemental analysis diagram, and e is a particle size distribution diagram;

[0056] Figure 5 1 shows the X-ray diffraction spectrum and X-ray photoelectron spectrum of the near-infrared light-responsive nanozyme of Example 2 of the present invention; in the figure, a is the X-ray diffraction spectrum, and b is the X-ray photoelectron spectrum;

[0057] Figure 6 Result diagram showing the ability of the near-infrared light-responsive nanozyme of Example 3 of the present invention to produce superoxide anions;

[0058] Figure 7 A result diagram showing the ability of the near-infrared light-responsive nanozyme of Example 3 of the present invention to produce hydroxyl radicals;

[0059] Figure 8 Graph showing the antibacterial experimental results of the near-infrared light-responsive nanozyme of Example 4 of the present invention;

[0060] Fig. 9 This is a diagram of a biofilm inhibition experiment of the near-infrared light-responsive nanozyme of Example 5 of the present invention;

[0061] Fig.10 Graph showing bacterial survival rate on the surface of a titanium rod with near-infrared light-responsive nanozyme spin-coated thereon in Example 6 of the present invention;

[0062] Fig.11 The results of the cytotoxicity experiment of near-infrared light-responsive nanozymes are shown;

[0063] Fig.12 The hematoxylin & eosin staining photos of the main organs of mice after being treated with titanium rods spin-coated with near-infrared light-responsive nanozymes;

[0064] Fig.13 Show the comparison of antibacterial performance;

[0065] Fig.14 Shows the solid UV-visible-near-infrared absorption spectra of near-infrared light-responsive nanozymes prepared with different proportions of silver phosphate (Ag3PO4) and silver sulfide (Ag2S). DETAILED DESCRIPTION

[0066] The present invention provides near-infrared light-responsive nanozymes, preparation methods and applications thereof. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve. It should be particularly noted that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0067] The near-infrared light-responsive nanozyme of the present invention can effectively prevent and reduce bacterial infection and biofilm formation of implant materials;

[0068] The near-infrared light-responsive nanozyme of the present invention is prepared by forming a composite nanomaterial consisting of Ag3PO4 nanoparticles and Ag2S quantum dots;

[0069] Ag2S quantum dots were prepared by the following method: 76.8 mg of AgDDTC, 30 g of octadecene and 6 g of dodecanethiol were added to a 100 ml three-necked flask and stirred vigorously under argon protection, then heated to 100°C and maintained for 10 minutes to remove water, then the temperature was raised to 170°C, after the solution color completely darkened, maintained for 10 minutes and then cooled to room temperature, then acetone was added to precipitate and separate the product to obtain the product, i.e., oil-phase dispersed Ag2S quantum dots;

[0070] The ligand exchange of Ag2S quantum dots was carried out by the following method: 0.5 g of maleic acid, 0.05 g of citric acid and 30 mg of oil-phase dispersed Ag2S quantum dots were dissolved in a mixed solution of chloroform and DMF (volume ratio of 1:1, total 50 mL). The mixture was kept at 30 °C and stirred for 24 hours, and then the product was collected by centrifugation and redispersed in distilled water, i.e., water-phase dispersed Ag2S quantum dots;

[0071] The near-infrared light-responsive nanozyme was prepared by the following method: 1.87 mmol of AgNO3 was dissolved in 40 ml of distilled water, and 0.315 g of HMT and aqueous dispersed Ag2S quantum dots (6% of the mass of AgNO3) were added to the above solution under vigorous stirring. Then, a 0.15M K3PO4 aqueous solution was added dropwise to the above solution, and a black precipitate was formed after stirring for 4 hours. The precipitate was washed three times with distilled water. Then, 0.1 g of PVP K30 was stirred with the above precipitate in distilled water for 12 hours, and finally the precipitate was washed three times with distilled water and stored in an oven at 60°C to obtain the product, i.e., the near-infrared light-responsive nanozyme;

[0072] The present invention also provides the use of the above-mentioned near-infrared light-responsive nanozyme material in an antibacterial coating for the surface of an implant, which is suitable for preventing and reducing bacterial infection and biofilm formation of implant materials. The specific method of use is: directly spin-coating the near-infrared light-responsive nanozyme material on the surface of the implant material, without special requirements.

[0073] The test materials used in the present invention are all common commercial products and can be purchased on the market. The present invention is further described below in conjunction with the embodiments:

[0074] Example 1 Preparation of Nanozyme

[0075] 1. Preparation of Ag2S quantum dots

[0076] 76.8 mg of AgDDTC (silver diethyldithiocarbamate, 98%), 30 g of octadecene (90%) and 6 g of dodecanethiol (98%) were added to a 100 ml three-necked flask and stirred vigorously under argon protection, then heated to 100° C. and maintained for 10 minutes to remove water, then the temperature was raised to 170° C., and after the solution color completely darkened, it was maintained for 10 minutes and then cooled to room temperature, and then acetone was added to precipitate and separate the product, as shown in FIG. Figure 2 As shown, the obtained product is oil-phase monodispersed Ag2S quantum dots with a diameter of about 4nm and typical 0.22nm and 0.26nm lattice fringes of Ag2S materials. Subsequently, 0.5 grams of maleic acid (99%), 0.05 grams of citric acid (99.5%) and 30 milligrams of oil-phase dispersed Ag2S quantum dots (wherein the concentration of Ag2S is 0.6mg / mL) were dissolved in a mixed solution of chloroform and DMF (DMF is N,N-dimethylformamide, the volume ratio of chloroform and DMF is 1:1, a total of 50mL). The mixture was maintained at 30°C and stirred for 24 hours, and then the product was collected by centrifugation and redispersed in distilled water to obtain water-phase dispersed Ag2S quantum dots.

[0077] 2. Preparation of Nanozymes

[0078] 1.87 mmol of AgNO3 (99.8%) was dissolved in 40 ml of distilled water (the concentration of AgNO3 was about 7.94 mg / mL at this time), and 0.315 g of HMT (hexamethylenetetramine, 99%) and Ag2S quantum dots dispersed in the aqueous phase (the added mass of Ag2S quantum dots was 6% of the added mass of AgNO3) were added to the above solution under vigorous stirring. Then, a 0.15M aqueous solution of K3PO4 (tripotassium phosphate hydrate, analytical grade) was added dropwise to the above solution (a total of 40 mL was added, i.e., 1.27 g of K3PO4 was involved in the reaction), and a black precipitate was formed after stirring for 4 hours. The precipitate was washed three times with distilled water. Then, 0.1 g of PVPK30 (polyvinyl pyrrolidone K30) was stirred with the above precipitate in distilled water for 12 h, and finally the precipitate was washed three times with distilled water and stored in an oven at 60°C to obtain a near-infrared light-responsive nanozyme;

[0079] 3. Preparation of Ag3PO4 nanoparticles (without Ag2S quantum dots):

[0080] As a control, Ag3PO4 nanoparticles were prepared by the following method: 1.87 mmol of AgNO3 (99.8%) was dissolved in 40 ml of distilled water, and 0.315 g of HMT (99%) was added to the above solution under vigorous stirring, and the whole solution immediately turned milky white. Then, a 0.15M K3PO4 (tripotassium phosphate hydrate, analytical grade) aqueous solution was added dropwise to the above solution, and after stirring for 4 hours, a golden precipitate was formed. The precipitate was washed three times with distilled water. Then, 0.1 g of PVPK30 was stirred with the above precipitate in distilled water for 12 hours, and finally the precipitate was washed three times with distilled water and stored in an oven at 60°C to obtain Ag3PO4 nanoparticles;

[0081] like Figure 3 As shown, the diameter of the Ag3PO4 nanoparticles is about 80-150 nm, and has the typical 0.21 nm and 0.27 nm lattice fringes of the Ag3PO4 material;

[0082] like Figure 4 As shown, the average particle size of the near-infrared light-responsive nanozyme is about 105nm, and it has the typical 0.26nm and 0.27nm lattice fringes of Ag2S material and Ag3PO4 material. Combined with the distribution of multiple elements shown in the elemental analysis, it can be considered that the Ag2S quantum dots are evenly distributed on the surface of Ag3PO4 nanoparticles;

[0083] like Figure 5 As shown, X-ray photoelectron spectroscopy proves that Ag2S quantum dots and Ag3PO4 nanoparticles form a composite nanomaterial, namely, near-infrared light-responsive nanozymes.

[0084] Example 2 Nanozyme Performance Determination

[0085] 1. The ability of near-infrared light-responsive nanozymes to produce superoxide anions under near-infrared light (808nm or 1064nm)

[0086] The ability of near-infrared light-responsive nanozymes to produce superoxide anions under near-infrared light (808 nm or 1064 nm) was investigated using electron spin resonance technology. 2,2,6,6-tetramethyl-4-piperidone (TEMP) was used as a free radical scavenger. The nanozyme was mixed with the free radical scavenger (33 mM) and irradiated with near-infrared light (1 W / cm 2 ) for 10 minutes, and then the characteristic signals of the samples were detected by electron spin resonance spectrometer.

[0087] like Figure 6As shown in the figure, Ag2S quantum dots do not have photocatalytic activity and only have the characteristics of near-infrared light absorption, so they do not produce superoxide anions under the irradiation of near-infrared light. Although Ag3PO4 nanoparticles have photocatalytic activity, they cannot absorb near-infrared light, so they cannot produce superoxide anions under the irradiation of near-infrared light, and therefore do not have near-infrared light-responsive oxidase activity. On the contrary, near-infrared light-responsive nanozymes (Ag2S-Ag3PO4) can absorb near-infrared light and stimulate the photocatalytic activity of Ag3PO4 nanoparticles through the electron transfer process. Therefore, they can produce a large amount of superoxide anions under the irradiation of 808nm or 1064nm near-infrared light, and exert effective near-infrared light-responsive oxidase activity.

[0088] 2. The ability of near-infrared light-responsive nanozymes to produce hydroxyl radicals under near-infrared light (808nm or 1064nm)

[0089] The ability of near-infrared light-responsive nanozymes to generate hydroxyl radicals under near-infrared light (808 nm or 1064 nm) was investigated using electron spin resonance technology. 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was used as a free radical scavenger. The nanozymes were mixed with the free radical scavenger (33 mM) and then irradiated with near-infrared light (1 W / cm 2 ) for 10 minutes, and then the characteristic signals of the samples were detected by electron spin resonance spectrometer.

[0090] like Figure 7 As shown in the figure, Ag2S quantum dots do not have photocatalytic activity and only have the property of near-infrared light absorption, so they do not produce hydroxyl radicals under the irradiation of near-infrared light. Although Ag3PO4 nanoparticles have photocatalytic activity, they cannot absorb near-infrared light, so they cannot produce hydroxyl radicals under the irradiation of near-infrared light, and therefore do not have near-infrared light-responsive oxidase activity. On the contrary, near-infrared light-responsive nanozymes (Ag2S-Ag3PO4) can absorb near-infrared light and stimulate the photocatalytic activity of Ag3PO4 nanoparticles through the electron transfer process. Therefore, they can produce a large amount of hydroxyl radicals under the irradiation of 808nm or 1064nm near-infrared light, and exert effective near-infrared light-responsive oxidase activity.

[0091] 3. Antibacterial effect of near-infrared light-responsive nanozymes

[0092] Weigh 5 g of tryptone, 5 g of sodium chloride and 2.5 g of yeast extract, put them into a conical flask, add 500 mL of deionized water, transfer to a sterilizer, sterilize for 20 min, cool to room temperature for use, and obtain LB medium.

[0093] Prepare solid LB medium and spread on plates: weigh 5g of tryptone, 5g of sodium chloride, 2.5g of yeast extract and 7.5g of agar, put them into a conical flask, add 500mL of deionized water, transfer to a sterilizer, and sterilize for 20 minutes. Transfer the medium to a culture dish while it is still hot, cool it down, turn it upside down and put it in the refrigerator for later use.

[0094] Methicillin-resistant Staphylococcus aureus will be used as a model to study the antibacterial effect of near-infrared light-responsive nanozymes. The strain was added to a conical flask containing LB medium and cultured overnight at 37°C until the OD 600nm reached 1.0. The cultured bacterial solution was diluted to 10 6 CFU / mL, and co-cultured with near-infrared light-responsive nanozymes (50 μg / mL) for 30 minutes, and then irradiated with 808 nm or 1064 nm laser for 5 minutes (1 W / cm 2 ), and then continue to co-cultivate for 3 hours, then dilute the above culture solution 1000 times, transfer 200 μL to LB solid culture medium, and spread it evenly with a spreader, and after culturing the coated solid culture medium at 37°C for 24 hours, count the number of bacterial colonies.

[0095] The results showed that the near-infrared light-responsive nanozyme had a good bactericidal effect on methicillin-resistant Staphylococcus aureus. Figure 8 shown.

[0096] 4. Effect of near-infrared light-responsive nanozymes in preventing biofilm formation

[0097] The methicillin-resistant Staphylococcus aureus strain was cultured in LB medium at 37°C overnight until the OD 600nm reached 1.0. Then 10μL of bacterial solution and 990μL of TSB medium were added to a 24-well plate and co-cultured at 37°C for 48 hours without shaking. Fresh culture medium was replaced every 24 hours, and biofilms attached to the bottom of the well plate could be observed after 48 hours. Then, 1mL of PBS solution containing near-infrared light-responsive nanozymes (50μg / mL) was added to the well plate containing the biofilm. After 15 minutes of co-culture, the well plate was illuminated for 5 minutes using an 808nm or 1064nm laser (1W / cm 2 ), and then continued to co-culture for 3 hours. Finally, the biofilm was stained with crystal violet staining, and the biofilm formation was evaluated by measuring OD590nm. Fig. 9 As shown, near-infrared light-responsive nanozymes can effectively prevent the formation of biofilms.

[0098] 5. Anti-infection ability of near-infrared light-responsive nanozymes

[0099] The near-infrared light-responsive nanozyme was spin-coated on the surface of a titanium rod and pretreated with methicillin-resistant Staphylococcus aureus before being implanted subcutaneously in mice. One day later, the implant area was illuminated for 5 minutes using an 808nm or 1064nm laser (1W / cm 2 , directly irradiate the epidermis, near-infrared light in the second zone can effectively penetrate the skin and be absorbed by the nanozymes). After 5 days, the implanted titanium rods were taken out and placed in LB culture medium for culture. The bacterial survival rates on the titanium rods in different groups were counted by colony counting method. Fig.10 As shown, the near-infrared light-responsive nanozyme antibacterial coating used in the present invention for the surface of implants has good ability to resist infection of implant materials.

[0100] 6. Biosafety of near-infrared light-responsive nanozymes

[0101] The cytotoxicity experiment of the near-infrared light-responsive nanozyme and the hematoxylin & eosin staining of the main organs of mice after they were treated with the titanium rod of the near-infrared light-responsive nanozyme were used to detect the cytotoxicity of the nanozyme.

[0102] Depend on Fig.11 and Fig.12 It can be seen that the near-infrared light-responsive nanozyme of the present invention has excellent biosafety and does not cause toxicity at the living level. Considering the level of inhibition of pathogens, a concentration greater than 50 μg / mL will produce cytotoxicity without light irradiation, but has a good bactericidal effect, so this concentration was selected as the experimental concentration ( Fig.11 ).

[0103] Example 3 Comparison and optimization in the preparation of near-infrared light-responsive nanozymes

[0104] The present invention prepares a graphene oxide (GO) / silver phosphate (Ag3PO4) / chitosan (CS) nanocomposite (GO / Ag3PO4 / CS); and prepares an Ag2S / Ag3PO4 composite photocatalyst (Ag2S / Ag3PO4 bulk material) as a comparison according to the preparation method in CN102824921A;

[0105] Depend on Fig.13 It can be seen that the nanocomposite composed of graphene oxide (GO) / silver phosphate (Ag3PO4) / chitosan (CS) cannot inhibit bacteria, and does not have antibacterial function under 808nm light and 1064nm light.

[0106] Compared with GO / Ag3PO4 / CS, the near-infrared light-responsive nanozyme prepared in the present invention has excellent bactericidal activity under illumination in the near-infrared region II and region I (1064nm laser excitation and 808nm) ( Fig.13 ). This is because the silver phosphate (Ag3PO4) material only has the ability to absorb near-infrared light and near-infrared zone II light, but its ability to generate active oxygen is insufficient. The silver sulfide (Ag2S) component in the near-infrared light-responsive nanozyme of the present invention can very effectively transfer electrons with the silver phosphate (Ag3PO4) component, thereby efficiently generating active oxygen components, and acting as a near-infrared zone II light-controlled nanozyme to remove bacteria.

[0107] However, Ag2S / Ag3PO4 bulk materials do not have infrared light response and antibacterial function (such as Fig.13 ), which may be due to the fact that nano-scale catalysts often have better dispersibility, larger specific surface area, better near-infrared light absorption and higher catalytic activity. The composite material of the present invention has excellent near-infrared / near-infrared second-zone light absorption ( Fig.14 ).

[0108] In addition, the present invention prepared silver phosphate (Ag3PO4)-silver sulfide (Ag2S) nanocomposites with various proportions, and found that the composite material with a content of 6% (the added mass of silver sulfide Ag2S is 6% of the added mass of silver phosphate) has the best light absorption capacity ( Fig.14 ). The surfactants used in the preparation of nanozymes were screened and their proportions were adjusted. The specific surfactants used included polyethylene glycol (PEG) and polyvinyl pyrrolidone (PVP); the molecular weights of the polyethylene glycols used were 400, 1000, 2000, 5000, and 10000, respectively; the types of polyvinyl pyrrolidone (PVP) were PVP K15, PVP K30, PVP K60, and PVP K90; the dosage was optimized based on different types of surfactants. Specifically, the amount of surfactant added was adjusted so that the mass of silver sulfide Ag2S was 5.02%, 10.15%, 15.32%, 19.06%, 30.85%, 40.32%, and 50.01% of the mass of PEG added; the mass of silver sulfide Ag2S was 5.02%, 10.15%, 15.32%, 19.06%, 30.85%, 40.32%, and 50.01% of the mass of PVP added; the results showed that polyvinyl pyrrolidone (PVP) surfactants were better than polyethylene glycol, and the dispersibility of the nanozyme prepared by polyethylene glycol was very poor; on this basis, it was found that when PVP K30 was used and the mass of Ag2s was 19.06% of the amount of polyvinyl pyrrolidone K30 added, the effect was optimal and the dispersibility of the prepared nanozyme was the best.

[0109] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A light-responsive nanozyme, characterized in that: include: Ag2S, Ag3PO4 and surfactants.

2. The light-responsive nanozyme according to claim 1, characterized in that The surfactant includes polyethylene glycol and / or polyvinyl pyrrolidone.

3. The light-responsive nanozyme according to claim 1 or 2, characterized in that The light-responsive nanozyme is a satellite structure with Ag3PO4 as the core.

4. The method for preparing the light-responsive nanozyme according to any one of claims 1 to 3, characterized in that: The steps include: Step 1, silver ions react with Ag2S and phosphate in the presence of hexamethylenetetramine to obtain Ag3PO4 particles combined with Ag2S; Step 2: The Ag2S-bound Ag3PO4 particles are wrapped with polyvinylpyrrolidone K30 to obtain the light-responsive nanozyme.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the salt compound containing the silver ion, hexamethylenetetramine, Ag2S, and the salt compound containing the phosphate is (0.1-0.5): (0.1-0.5): (180-200): (1.0-1.5).

6. The preparation method according to claim 4, characterized in that: The Ag2S is prepared from silver diethyldithiocarbamate and dodecanethiol.

7. The preparation method according to claim 4 or 6, characterized in that: The mass ratio of the silver diethyldithiocarbamate to dodecanethiol is 1:(60-80).

8. A nanozyme preparation, characterized in that Including at least one of a preservative, a stabilizer, an antioxidant and / or a buffer and at least one of the following I) to II): I), the light-responsive nanozyme according to any one of claims 1 to 3; II), a light-responsive nanozyme prepared by the preparation method according to any one of claims 4 to 7.

9. An antimicrobial composition, characterized in that Including at least one of a) to c) and an antibacterial substance: a), the light-responsive nanozyme according to any one of claims 1 to 3; b) A light-responsive nanozyme prepared by the preparation method according to any one of claims 4 to 7; c) The nanozyme preparation according to claim 8.

10. Use of at least one of the following i) to iii) in reducing bacterial infection and biofilm formation in implant materials: i), the light-responsive nanozyme according to any one of claims 1 to 3; ii), a light-responsive nanozyme prepared by the preparation method according to any one of claims 4 to 7; iii) the nanoenzyme preparation according to claim 8; iv) The antibacterial composition according to claim 9.

11. A method for reducing bacterial infection and biofilm formation, characterized in that: Including using at least one of the following A) to D): A), the light-responsive nanozyme according to any one of claims 1 to 3; B), a light-responsive nanozyme prepared by the preparation method according to any one of claims 4 to 7; C) The nanozyme preparation according to claim 8; D) The antibacterial composition according to claim 9.

Citation Information

Patent Citations

  • Preparation method of Ag2S / Ag3PO4 composite photocatalyst

    CN102824921A